2002
DOI: 10.1017/s1351324902003005
|View full text |Cite
|
Sign up to set email alerts
|

Parameter optimization for machine-learning of word sense disambiguation

Abstract: Link to this article: http://journals.cambridge.org/abstract_S1351324902003005How to cite this article: V. HOSTE, I. HENDRICKX, W. DAELEMANS and A. VAN DEN BOSCH (2002). Parameter optimization for machine-learning of word sense disambiguation. Natural Language Engineering, 8, pp 311-325 AbstractVarious Machine Learning (ML) approaches have been demonstrated to produce relatively successful Word Sense Disambiguation (WSD) systems. There are still unexplained differences among the performance measurements of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“…Such relations have been reported in [5]. For example, if the baseline ambiguity were high (e.g., 95/100), it would be hard for any algorithm to learn to correctly classify the additional five cases.…”
Section: Troublesome Instancesmentioning
confidence: 67%
See 4 more Smart Citations
“…Such relations have been reported in [5]. For example, if the baseline ambiguity were high (e.g., 95/100), it would be hard for any algorithm to learn to correctly classify the additional five cases.…”
Section: Troublesome Instancesmentioning
confidence: 67%
“…This majority sense performance, also called lexical default [5], served as the baseline for our study. We choose 65% because others have found that high majority sense results in a very skewed dataset that provides insufficient examples to automatically learn from [3].…”
Section: Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations